2021
DOI: 10.1080/16549716.2021.1908064
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and health in urban informal settlements in low- and middle-income countries – a scoping review of health impacts and adaptation strategies

Abstract: Background : Climate change affects human health with those with the least resources being most vulnerable. However, little is known about the impact of climate change on human health and effective adaptation methods in informal settlements in low- and middle-income countries. Objective : The objective of this scoping review was to identify, characterize, and summarize research evidence on the impact of climate change on human health in informal settlements and the available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
0
20
0
2
Order By: Relevance
“…More elaborate approaches stress test options under different climate scenarios, to support decisions and trade-offs between robustness, cost, safety margins, flexibility and regret (Hallegatte et al, 2019). A key consideration is to ensure, as was done in our study, that attention is focused on those people most likely to be exposed to climate impacts, and who may have lower ability to cope and adapt (Levy et al, 2018;Højgaard Borg et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…More elaborate approaches stress test options under different climate scenarios, to support decisions and trade-offs between robustness, cost, safety margins, flexibility and regret (Hallegatte et al, 2019). A key consideration is to ensure, as was done in our study, that attention is focused on those people most likely to be exposed to climate impacts, and who may have lower ability to cope and adapt (Levy et al, 2018;Højgaard Borg et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There are major knowledge gaps on how to guide and develop interventions to improve climate change adaptation and resilience in relation to health at the local community level. A review of the literature from 2020 on health implications of climate change found just seven studies on climate change and health in LMICs [20]. The review identified studies reporting on food insecurity [21][22][23], water insecurity [22,23], illness [23][24][25], mental health [23], injuries from extreme weather events [22], and heat-exposure [26] related to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Many perceived environmental stressors resulting from changes in climate directly affect brain function and mental well-being, as seen in studies showing that people living in flooded areas reported poor mental health as well as the more commonly reported physical ailments. 8…”
Section: Mental Health Impacts Of Climate Changementioning
confidence: 99%
“…Many perceived environmental stressors resulting from changes in climate directly affect brain function and mental well-being, as seen in studies showing that people living in flooded areas reported poor mental health as well as the more commonly reported physical ailments. 8 Common outcomes of intense or persistent stressors include anxiety disorders, post-traumatic stress disorder, suicidal ideation and depression. 9 There is evidence supporting the correlation of extreme heat with violent behaviour towards themselves and others, increased rates of suicide and hospital admissions for self-harm, and tripled risk of mortality for those with pre-existing mental health conditions.…”
Section: Mental Health Impacts Of Climate Changementioning
confidence: 99%